Pengadopsian Konsep Extended Femicide Ke Dalam Sistem Hukum Indonesia Sebagai Upaya Mengisi Kekosongan Hukum Perlindungan Perempuan - Razaqa, Sultan Arkana; Bella Adiratna Humaira Diani Supnadi; Karina Anugrah Putri Indra Kusumawati; Khairunisa Tiara Arifin (Indonesian Journal of Criminal Law, 2025)
Femicide is the most extreme form of gender-based violence within patriarchal societies, where women often become victims of unequal power relations. This research departs from the fact that Indonesian criminal law has not specifically recognized acts of femicide, namely the killing of women both in intimate and non-intimate relationships that is motivated by gender. Using a socio-legal approach and a normative juridical method, this study examines the legal vacuum through analysis multiple court decisions containing elements of femicide. The findings show that most judges still view the killing of women as an ordinary criminal act, without considering the dimension of gender inequality underlying it, while others have identified traits of what constitutes femicide, though inconsistently. Judicial reasoning predominantly focuses on normative reasoning, diminishing the importance of the context of gender-based violence. This condition indicates that gender sensitivity has not yet been formed in Indonesia’s judicial practice and legal system. This research emphasizes the importance of a legal instrument to fill the gap, one of the possibilities being the establishment of a Supreme Court Regulation (Perma) that provides guidance for judges to identify and consider elements of femicide in cases involving the killing of women.